Highly Efficient Bulky α‐Diimine Palladium Complexes for Suzuki‐Miyaura Cross‐Coupling Reaction. Issue 3 (13th March 2017) - Huo, Ping; Li, Jingbo; Liu, Wanyun; Mei, Guangquan
Abstract: A series of bulky 9, 10‐dihydro‐9, 10‐ethanoanthracene‐11, 12‐diimine methyl palladium chloride complexes (C1—C6 ) with different steric and electronic substituent have been applied in Suzuki‐Miyaura cross‐coupling reactions. The influence of these substituents was investigated by comparing the catalytic performance of the complexes in the cross‐coupling reactions and it can be found that the complex with bulky and electron‐donating substituent is facilitated for the cross‐coupling reaction of aryl halides with arylboronic acids under ambient atmosphere. The most active complex shows a wide substrate scope in excellent yields using very low catalyst concentration of 0.01 mol%. Abstract : The 9, 10‐dihydro‐9, 10‐ethanoanthracene‐11, 12‐diimine palladium complex with bulky and electron‐donating substituent is facilitated for the cross‐coupling reaction of aryl halides with arylboronic acids under ambient atmosphere. The most active complex shows a wide substrate scope in excellent yields using very low catalyst comcentrations of 0.01 mol%.